Ghrelin regulation of glucose metabolism. (3rd April 2019) - Gray, Sarah M.; Page, Laura C.; Tong, Jenny
Abstract : Ghrelin and its receptor, the growth hormone secretagogue receptor 1a (GHSR1a), are implicated in the regulation of glucose metabolism via direct actions in the pancreatic islet, as well as peripheral insulin‐sensitive tissues and the brain. Although many studies have explored the role of ghrelin in glucose tolerance and insulin secretion, a complete mechanistic understanding remains to be clarified. This review highlights the local expression and function of ghrelin and GHSR1a in pancreatic islets and how this axis may modulate insulin secretion from pancreatic β‐cells. Additionally, we discuss the effect of ghrelin on in vivo glucose metabolism in rodents and humans, as well as the metabolic circumstances under which the action of ghrelin may predominate.